Parent's perspectives of the pathway to diagnosis of childhood cancer: a matter of diagnostic triage - Line Hjøllund Pedersen; Ayo Wahlberg; Marie Cordt; Kjeld Schmiegelow; Susanne Oksbjerg Dalton; Hanne Bækgaard Larsen (BMC, 2020)
Abstract Background Early diagnosis is crucial for the treatment of childhood cancer as it in some cases can prevent progression of disease and improve prognoses. However, childhood cancer can be difficult to diagnose and barriers to early diagnosis are multifactorial. New knowledge about factors influencing the pathway to diagnosis contribute to a deeper understanding of the mechanisms that influence this time span. Qualitative research in the field is sparse but can be expected to lead to additional useful insights that could contribute to efforts shorten time to diagnosis. The purpose of this study was to explore parents' experiences of the pathway to diagnosis in the time between their noticing bodily or behavioural changes and their child's diagnosis. Methods The study is a qualitative interview study carried out in large Danish hospital. Thirty-two interviews with a total of 46 parents of children with cancer were included for analysis. The children were diagnosed with haematological cancers (n = 17), solid tumours (n = 9) or brain tumours (n = 6). Data were analysed applying the theoretical model of pathways to treatment and an inductive-deductive approach. A revised 'diagnostic triage' model was developed and validated by member checking. Results The pathway to diagnosis was influenced by various factors which we present as consistent parts of a new diagnostic triage model. Each factor impacts the level of urgency assigned to bodily and behavioural changes by parents, general practitioners and specialists. The model of diagnostic triage was developed and validated to understand mechanisms influencing time from the point parents notice changes in their child to diagnosis. The model identifies dynamic movement between parental triage in everyday life and professional triage in a healthcare system, both affecting appraisal and case escalation according to: 1) the nature of bodily and behavioural changes, 2) parental intuition, 3) social relations, 4) professional-child-parent interaction, and 5) specialist-child-parent interaction. Conclusions Diagnostic triage is a model which explains mechanisms that shape the pathway to diagnosis. It is a contribution aimed at supporting the clinical diagnostic process, that ultimately could ensure more timely testing, referral and diagnosis, and also a novel theoretical framework for future research on diagnostic pathways.